Analisis Butir Soal HOTS Elemen Prinsip dan Konsep Dasar Akuntansi dan Perbankan Melalui Program Anates - Gita Putri Rahayu; Hakim, Luqman; Pratiwi, Vivi; Nafilah, Fatma Nisa; Sari, Naila Atika (Widya Balina, 2025)
This study aims to analyze multiple-choice questions related to phase e elements, namely the Principles and Basic Concepts of Accounting and Basic Banking, using the Anates program. The study involved 20 participants, consisting of college students and vocational high school students. The Anates application program serves as a tool to process academic evaluation data accurately and efficiently. The method used in this study is quantitative and is described descriptively, resulting in analytical findings including weighted data scores, test reliability, discriminative power, difficulty level, validity level, and distractor quality. The results from the Anates program make it easier for teachers to evaluate the quality of learning and develop more focused, innovative, and student-centered teaching plans. This research is expected to provide benefits in improving students' accounting knowledge, and teachers are expected to be able to adjust their teaching methods and strategies dynamically, thereby supporting the optimal improvement of students' learning outcomes in this digital era.